Design of thermoplastic vulcanizates induced by metal-ligand coordination towards enhanced mechanical properties and shape memory behavior. (December 2020) - Huang, Jiarong; Gong, Zhou; Peng, Tao; Cao, Liming; Chen, Yukun
Abstract: It remains a challenge to prepare thermoplastic vulcanizates (TPVs)-based composites with multi-functions and enhanced mechanical properties simultaneously. Here, metal-ligand coordination was introduced into dynamic vulcanization to fabricate styrene-acrylonitrile copolymer (SAN)/butadiene acrylonitrile rubber (NBR)/iron chloride (FeCl3 ) TPVs. Fe 3+ could not only interact with the nitrile groups (-CN) of NBR to cross-link the rubber phase, but also interact with the –CN of SAN to realize the interfacial compatibilization, enhancing the mechanical properties of the TPVs. Significantly, the dynamic nature of Fe 3+ -CN interactions endowed the TPVs with reconfigurable network-like rubber phase and excellent recycling ability. The coordination interaction and network-like structure of the NBR phase enabled the TPVs into shape memory materials with shape recovery ratio of 91.53%. We propose a novel technique to prepare TPVs with high performance and multi-functionality, and it may expand the research scope of dynamic vulcanization. Highlights: Metal coordination bonds were innovatively utilized to initiate dynamic vulcanization. FeCl3 acted as curing agent and filler to cure and reinforce the NBR network. FeCl3 also acted as compatibilizer to realize the interfacial compatibilization. The composites exhibited enhanced mechanical property and shape memory property.